Keterampilan Membaca Siswa Kelas IX dalam Meningkatkan Kemampuan Membaca Cerpen Payung Karya Dewi Susilowati di SMPN 141 Jakarta - Lathifah Sekar Fitriarini; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the reading skills of class IX students in improving their ability to read short stories, besides encouraging students to improve their ability to analyze literary elements in short stories. The method used in the research is descriptive qualitative. Data sources were obtained through observation and distribution of questionnaires, then analyzed using random sampling techniques. The results of the research show that reading ability is an important aspect in individual development, including the skills of identification, comprehension, evaluation and application of information contained in texts. A student's level of reading ability has a direct impact on success in various areas of life, including education, career, and daily life.